“Encores me frissonne et tremble le coeur dedans sa capsule”: Rabelais’s Anatomy of Emotion and the Soul - Lacore-Martin, Emmanuelle (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
This article examines the role of anatomical references in the representation of emotion and argues that they constitute textual markers of the Rabelaisian view of the relationship between the body and the soul, and the nature of the soul itself. By analyzing the ancient models of natural philosophy and medicine on which Rabelais draws—Galen, in particular—and by contextualizing Rabelais’s thinking within contemporary debates on the faculties of the soul, the article aims to shed light on his representation of the intersection between material and immaterial processes within the human body. Instead of trying to reconcile potentially contradictory aspects of these ancient models with the Christian faith, Rabelais’s prose is informed by an intuitive understanding of ancient philosophy. His exploitation of the Galenic concept of the animal spirits gives us invaluable insights into the influence of materialist representations of the soul on Rabelais’s thinking.